The Role Of Job Satisfaction As A Mediation Variable In The Effect Of Psychological Capital And Person–Organization Fit On Work Engagement Of Generation Z Employees In The Footwear Retail - Fithrotul Aulia; Dewie Tri Wijayati; Andre Dwijanto Witjaksono (LP2M IAIN Palopo, 2026)
This study analyzes the role of job satisfaction as a mediator in the effect of psychological capital and person–organization fit on work engagement among Generation Z employees in the footwear retail industry. Methods: This research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Data were collected through structured questionnaires distributed to 103 Generation Z employees of an Indonesian footwear retail company, selected via purposive sampling. Results: Psychological capital and person–organization fit significantly predict job satisfaction, with person–organization fit as the strongest predictor. Job satisfaction significantly predicts work engagement. Psychological capital does not directly affect work engagement, while person–organization fit does. Job satisfaction fully mediates the psychological capital–engagement relationship and partially mediates the person–organization fit–engagement relationship. Implications: Person–organization fit emerges as the dominant predictor and job satisfaction as the critical psychological bridge through which internal and contextual resources convert into engagement. Footwear retail managers should prioritize cultural and value alignment in recruitment and retention, while developing psychological capital through coaching and training to indirectly enhance engagement via improved satisfaction.